Simultaneous preconcentration and determination of sulfonamide antibiotics in milk and yoghurt by dynamic pH junction focusing coupled with capillary electrophoresis - Semail, N.-F. (Elsevier B.V., 2022)
A dynamic pH junction was used in capillary electrophoresis (CE-DAD) to on-line preconcentrate, separate, and determine trace amounts of sulfonamide antibiotics (SAs) in milk and yoghurt samples in this study. A sample matrix with 0.15 acetic acid and 10 methanol (MeOH) at a pH of 4.0, and a background electrolyte (BGE) that contained 35 mM sodium citrate with 10 MeOH at a pH of 8.5, and an acidic barrage of 0.4 acetic acid with 10 MeOH at a pH of 2.5 were utilised to achieve a stacking effect for SAs through a dynamic pH junction. Under optimised conditions, the proposed preconcentration method showed good linearity (30â500 ng/mL, r2 â¥ 0.9940), low limits of detection (LODs) of 4.1â6.3 ng/mL, and acceptable analytes recovery (81.2â106.9) with relative standard deviations (RSDs) within 5.3â13.7 (n = 9). The limits of quantification (LOQs) were below the maximum residue limit approved by the European Union (EU) in this type of matrices. Sensitivity enhancement factors of up to 129 were reached with the optimised dynamic pH junction using CE with a diode array detector (DAD). The method was used to determine SAs in fresh milk, low-fat milk, full-cream milk, and yoghurt samples. Â© 2021 Elsevier B.V.